What Happened on the Workload Cause Burnout of Nurses in Royal Prima Hospital Medan - Sri Hartini; Cindy Cindy; Richard Bardo; Angelica Setiawan; Cynthia Lawrance (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The study is being conducted to determine the relationship between burnout and workload of nurses in Royal Prima Medan Hospital. There were 152 nurses from Royal Prima Medan Hospital, which were chosen using purposive sampling method. The hypothesis of this study were burnout had relationship with workload. This study used quantitative method. The data were collected using Workload Scale with 20 items and Burnout Scale with 29 items. Normality test and Linearity test were used as the assumption test. Data collected was analyzed using Pearson Correlation Product Moment, using SPSS 24 version for Windows. The result shown that there burnout had given 39.4 percent effective contribution in workload, the rest of 60.6 percent were influenced by other factors that were not included in this study. With this result, it was concluded that the hyphothesis of this study was accepted. University of Indonesia (MKK FKUI) in 2020, shows the fact that as many as 83 percent of health workers in Indonesia have experienced moderate and severe burnout syndrome which is psychologically at risk of disrupting the quality of life and work productivity in health services (fk.ui.ac.id). Based on the results of an interview on December 23, 2020 to 2 nurses at the Royal Prima Hospital, they stated that during the Covid-19 pandemic they worked more than their normal working hours. There are many outpatients and also many inpatients while the number of nurses is less so that the work pressure they feel is getting higher. Even the fear of contracting Covid makes them feel even more depressed and exhausted. The pressure and fatigue they experience makes them increasingly unproductive, unmotivated and bored with the demands and responsibilities of the work they currently carry.